The formulation of probiotic Lactobacillus acidophilus granule with acacia and sodium alginate as binding agents - Ari Widayanti; Lusi Susanah; Priyo Wahyudi (Pharmaciana, 2018)
Probiotics are living microorganisms that can have a positive impact on health when consumed in adequate amounts. This research aimed to determine the effect of different binders on the viability of Lactobacillus acidophilus, a member of Lactic Acid Bacteria (LAB). The probiotic granules were prepared with wet granulation method using mannitol as the filling ingredient. Formulas I-III used acacia as a binder (3%, 4%, and 5%), while Formulas IV-VI used sodium alginate (1%, 1.5%, and 2%). The probiotic granules produced from all formulas were evaluated for flow time, the angle of repose, compressibility, and LAB viability. The LAB viability test results showed that all of the six formulas met the probiotic requirements, i.e., at least 107 CFUs (Colony Forming Units) per gram. The viable LAB in Formulas I-VI were 3.94x107, 4.4x107, 2.7x107, 2.6x107, 3.5x107, and 2.3x107 CFU/g, respectively. The data were analyzed by comparing the average values of the One-Sample T-Test results, followed by Mann-Whitney test. The results revealed that each formula had different capacity in maintaining the viability of Lactobacillus acidophilus with different binders (i.e., acacia and sodium alginate) as a probiotic product. Formula II (4% of acacia) produced probiotic granules that met the requirements of compressibility and the angle of repose. However, its granular flow time exceeded the standard.